Performance evaluation of groundwater management instruments: the case of irrigation sector in Tunisia - Frija, Aymen; Dhehibi, B.; Chebil, A.; Villholth, Karen G. (2016)
Around 27% of aquifers in Tunisia are being overexploited. Groundwater extractions is mainly for the irrigation sector, where more than 40% of the water used for irrigation comes from GW sources. The objective of this study is to critically review and analyze GW management instruments adopted in Tunisia during the last four decades. Evaluation of current instruments was based on a set of criteria (the impact of the instrument on increasing water productivity, reducing aquifer withdrawals, acceptability of the instrument and its implementation cost) assessed through interviews with policy makers and experts, in addition to discussions at farmers' focus groups. Results show that regulatory instruments are widely used but weakly enforced, which can explain their limited impact. To be more effective, economic instruments need a better vertical interplay between different stakeholders. Analysis of stakeholders’ participation shows limited awareness by farmers and a lack of collective actions for GW management at local levels. The alignment of GW policies to other cross-sectorial policies, the enhancement of the vertical interplay between water users’ associations and local and national water administrations, and the horizontal integration of different water users and managers at the local and regional levels, are among the main recommendations of this study.